2024
DOI: 10.3390/cancers16030512
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Ferroptosis and Cuproptosis in Cancer: Dissecting Metal-Driven Mechanisms for Therapeutic Potentials

Jinjiang Wang,
Jiaxi Li,
Jiao Liu
et al.

Abstract: Iron (Fe) and copper (Cu), essential transition metals, play pivotal roles in various cellular processes critical to cancer biology, including cell proliferation, mitochondrial respiration, distant metastases, and oxidative stress. The emergence of ferroptosis and cuproptosis as distinct forms of non-apoptotic cell death has heightened their significance, particularly in connection with these metal ions. While initially studied separately, recent evidence underscores the interdependence of ferroptosis and cupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…The interplay between two forms of cell death, ferroptosis and cuproptosis, has garnered scienti c interest. Disruptions in their metabolic functions can lead to lethal consequences for cancer cells, triggering both ferroptosis and cuproptosis [57]. The mechanism of copper-dependent cell death is closely linked to mitochondrial respiration, initiated when copper binds directly to the lipoylated components of the tricarboxylic acid (TCA) cycle [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interplay between two forms of cell death, ferroptosis and cuproptosis, has garnered scienti c interest. Disruptions in their metabolic functions can lead to lethal consequences for cancer cells, triggering both ferroptosis and cuproptosis [57]. The mechanism of copper-dependent cell death is closely linked to mitochondrial respiration, initiated when copper binds directly to the lipoylated components of the tricarboxylic acid (TCA) cycle [11].…”
Section: Discussionmentioning
confidence: 99%
“…This binding sets off a series of events, including protein oligomerisation, loss of iron-sulfur cluster proteins, and proteotoxic stress, leading to cell death [58]. In addition, a connection between mitochondrial copper accumulation and the initiation of ferroptosis has been established [57].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, copper metabolism is considered a promising strategy for cancer therapy [16]. Furthermore, there exists mutual dependence between cuproptosis and ferroptosis [17]. Studies have revealed that in hepatocellular carcinoma, sorafenib and erastin upregulate protein lipoylation by inhibiting degradation of iron-sulfur cluster protein 1 (FDX 1) mediated by mitochondrial matrix-related protease, and reduce synthesis of intracellular copper chelator glutathione (GSH) by inhibiting cysteine input [18].…”
Section: Introductionmentioning
confidence: 99%